The New Avant-Garde in Italy : Theoretical Debate and Poetic Practices. - Picchione, John (Toronto Italian studies., 2014)
This study suggests that some of the contentious views proposed by the neoavanguardia anticipated a wide range of issues that continue to be significant and pressing to this day.